1973
DOI: 10.1128/iai.7.5.725-730.1973
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Stable L-Phase Variants of Staphylococcus aureus : Failure to Colonize Experimental Endocarditis in Rabbits

Abstract: Endocarditis was induced in the rabbit by the placement of a polyethylene catheter in the right heart. The catheter was filled with stable L-phase variants of Staphylococcus aureus to determine if the variant form would colonize the damaged endocardium and produce further tissue injury similar to that produced by the vegetative bacterial phase. No L-phase variants were recovered from cultures of blood or vegetations, although pure cultures of L-phase variants were obtained from all catheters, including one in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1974
1974
1992
1992

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…The commonest explanation is that sucrose protects cell wall-defective bacteria from osmotic lysis in blood containing antimicrobial agents or enzymes that act on the cell wall (14,28). Although evidence is lacking that wall-defective bacteria themselves are pathogenic (10,18), hypertonic media have been helpful in a small number of carefully selected cases in isolating conventional forms of bacteria from the blood of patients who have received cell wall-active antimicrobial agents (11). Such appeared to be the case in our patient with relapsing S. epidermidis endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…The commonest explanation is that sucrose protects cell wall-defective bacteria from osmotic lysis in blood containing antimicrobial agents or enzymes that act on the cell wall (14,28). Although evidence is lacking that wall-defective bacteria themselves are pathogenic (10,18), hypertonic media have been helpful in a small number of carefully selected cases in isolating conventional forms of bacteria from the blood of patients who have received cell wall-active antimicrobial agents (11). Such appeared to be the case in our patient with relapsing S. epidermidis endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of wall-defective microbial variants in the initiation and persistence of infection continues to be debated. We have demonstrated in animal experiments that the stable L-phase variants of Staphylococcus aureus were unable to initiate infection under the most favorable experimental conditions (5,12). Other investigators have reported the reversion of walldefective microbial variants to the vegetative bacterial phase in experimental animals (4,6,13) and it has been postulated that these revertants might be responsible for the perpetuation or persistence of infection.…”
mentioning
confidence: 70%
“…Why sucrose should be beneficial in some media or some ratios of blood to broth is unclear. One explanation is that sucrose protects cell wall-defective bacteria from osmotic lysis (14,15,30), but evidence for a pathogenic role of these bacteria is lacking (11,19). Hypertonic media have been helpful in a small number of cases in recovering bacteria from patients receiving cell wall-active antimicrobial agents (12).…”
Section: Discussionmentioning
confidence: 99%